Faktor-Faktor yang Memengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Wilayah Samsat Palembang IV - Fatama, Dinda Nafilah; Faridah, Faridah; Aprianti, Siska (Politeknik Negeri Jember, 2024)
The purpose of this study was to determine the effect of Tax Whitening, Samsat Around, Taxpayer Awareness and Taxpayer Knowledge on Taxpayer Compliance for Motorized Vehicles in Palembang IV City. The study population consists of all motorized vehicle taxpayers totaling 407,498 motorized vehicle taxpayers in the Palembang IV Samsat Region. Accidental sampling is the sample method used. Using the Slovin formula, the sample size was determined to be 100. Each sample was asked if they were willing to complete the questionnaire. SPSS software was used to perform multiple linear regression analysis on the data. Based on the results of the analysis, it is evident that tax bleaching, mobile samsat and taxpayer knowledge partially increase the compliance of WPKB in the Palembang IV Samsat area. Meanwhile, taxpayer awareness has no effect on WPKB compliance in the Palembang IV Samsat area.